Adsorption of Methyl Orange and Cr (VI) Onto Poultry Manure-Derived Biochar From Aqueous Solution - Ghani, Usman; Jiang, Wenjia; Hina, Kiran; Idrees, Atif; Iqbal, Meenal; Ibrahim, Muhammad; Saeed, Rashid; Irshad, M. Kashif; Aslam, Imran (Frontiers in Environmental Science, 2022)
In recent years heavy metals and other organic compounds pollution has increased and has become a considered able global problem due to their direct impacts on the aquatic ecosystem. This study aimed to see how efficient the poultry manure-derived biochar is in removing the chromium (VI) and methyl orange simultaneously from the aqueous solutions through adsorption. Chromium was present in the form of reactive ions such as HCrO4 and Cr2O72 at pH 2-6 values and was in stable form i.e. CrO4 at alkaline pH. In this study poultry manure-derived biochar prepared by slow pyrolysis method was used for the adsorption of methyl orange and hexavalent chromium from aqueous solutions. In this study biochar was synthesized by the slow pyrolysis of feedstock in a muffle furnace at 550 ℃ temperature with 2 mm particle size. This study provided the biochar with SBET 16.0921 m²/g rough stomata like pores with volume of 0.0074 cm³/g, pore diameter 1.84 nm, aromatic groups, and structural diversity. The as-prepared biochar used for simultaneous sorption of MO and Cr (VI) from solution. Batch adsorption was experiment conducted to investigate the adsorption efficiency and mechanisms were elucidated by fitting isotherm and kinetic models and results analysis along with the thermodynamics. The linear Langmuir well fitted with the experimental data having R2 value of 0.99 and 0.99 for MO and Cr respectively. From kinetics study, linear pseudo second order (PSO) highly fitted with obtained data with R2 of 0.951 and 0.952 for MO and Cr, respectively. The results analysis revealed that HCrO4 and Cr2O72 ions compete with the SO3 to attach on the surface of sorbent which leads to competitive adsorption of Cr (VI) and MO onto BC. Thermodynamic study presents the change in The adsorption process was monolayer physisorption, irreversible and endothermic. The surface functional groups had high affinity towards the HCrO4 and Cr2O72 than MO, causing competition between MO and Cr to adsorb. Hence it can be said that this material is environmental-friendly and economical sorbent for high adsorption efficiency.